EPIDEMIOLOGY OF RISK FACTORS OF ARTERIAL HYPOTENSION IN POPULATION ENGAGED IN FARMING ACTIVITY - Mamasoliev N.S; Tursunov J.Kh; Tursunov Kh.Kh; Saidkhojaeva J. G (Scholar Express Journals, 2023)
The criteria for a significant decrease in arterial pressure is considered to be an element of arterial pressure variability or a certain degree of manifestation. Implementation of various forms of epidemiologic research in order to establish the basis for new approaches to early diagnosis of arterial hypotension, to improve the prognosis, and to achieve high efficiency in prevention has become a necessity and a necessity for farmers in the conditions of Uzbekistan. In the regions of Uzbekistan, there is a great need and necessity to solve the problems of R&T in this approach. The lack of scientific study of this issue, especially among the large population of Uzbekistan engaged in farming, undoubtedly requires science to fill the "gap" in this direction.
Keywords: arterial hypotension; primary arterial hypotension; syncopal state; cardio comorbidity